2001
DOI: 10.1186/cc1058
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: On 7 December 1988, a severe earthquake hit in Armenia, a former republic of the Soviet Union (USSR); on 11 September 2001, a manmade attack of similar impact hit New York City. These events share similar implications for the role of the uninjured survivor. With basic training, the uninjured survivors could save lives without tools or resuscitation equipment. This article makes the case for teaching life-supporting first aid to the public in the hope that one day, should another such incident occur, they would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…6 According to European Resuscitation Council and First Aid guidelines, trained bystanders can reduce mortality and reduce morbidity until professional help arrives in cases of injury, sudden illness, or other life-threatening emergency. 7,8 Two reports on the September 11, 2001, New York attack 9 and July 7, 2005, London bombings 10 suggest that first aid provided by bystanders might have saved lives. During the Madrid 2004 bombings, approximately 67% of the injured arrived at hospitals in nonambulance vehicles, 11 potentially limiting or reducing injury, its long-term effects, and even death 12,13 that may have occurred while waiting for ambulances.…”
mentioning
confidence: 99%
“…6 According to European Resuscitation Council and First Aid guidelines, trained bystanders can reduce mortality and reduce morbidity until professional help arrives in cases of injury, sudden illness, or other life-threatening emergency. 7,8 Two reports on the September 11, 2001, New York attack 9 and July 7, 2005, London bombings 10 suggest that first aid provided by bystanders might have saved lives. During the Madrid 2004 bombings, approximately 67% of the injured arrived at hospitals in nonambulance vehicles, 11 potentially limiting or reducing injury, its long-term effects, and even death 12,13 that may have occurred while waiting for ambulances.…”
mentioning
confidence: 99%
“…This has been considered in some detail in Chapter 2. While much has been reviewed in relation to practical operational issues such as medical management (Shimazu et al, 1997;Crippen, 2001;Sever et al, 2002;Ashkenazi et al, 2005) and the fact that rescue efforts should be in place as early as possible (de Bruycker, Greco, Lechat et al, 1985;Tanaka, 1996), no significant literature has been found on the more specific issue of use of USAR resources by affected countries who have little or no understanding of them.…”
Section: Usar Operational Issuesmentioning
confidence: 99%